PEMBERDAYAAN SISWI SMK PENTINGNYA KONSUMSI TTD (TABLET TAMBAH DARAH) DI SEKOLAH X LIMO, DEPOK - Idiara Setya Yusdika; Sintha Fransiske Simanungkalit; Hendry Roris P Sianturi; Bernadin Dwi Mardiatmi (Universitas Mataram, 2023)
Adolescence is a transition period from childhood and adulthood from the age of 11 to 21 years. According to WHO, an individual teenager is still said to be a teenager when he is 10-19 years old. At the time of entering adolescence, they will experience a transitional period of mental, physical and reproductive development that can have an impact on general health status. Therefore, problems in adolescents are very important to note because good growth and development in adolescents forms optimal health status in adulthood. Anemia is a condition when the level of hemoglobin (Hb) in the blood is low. Compared to young men, young women are more likely to experience anemia caused by menstrual factors. The menstrual cycle in adolescent girls will increase every month, causing an increase in monthly iron expenditure. Adolescent girls have unhealthy food consumption habits, causing the diversity of food substances to be not fulfilled by the body for the formation of hemoglobin (Hb). The purpose of this activity is to increase the knowledge of young women regarding the consumption of Blood Add Tablets (TTD) and food sources of Fe in the UPTD area of the Limo Health Center, Depok, West Java. The results obtained from this activity are an increase in the posttest score of 100%. The results obtained from the Wilcoxon test is the value of Sig. 0.000 < 0.05. The conclusion from the tests carried out was that there was a difference in knowledge between before and after the intervention regarding the consumption of Blood Supplementary Tablets (TTD) and food sources of Fe.